Analisis Pelakasanaan Pembelajaran Daring Pada Peserta Didik Kelas V di SD Negeri Cemoro Kabupaten Boyolali Tahun Pelajaran 2020/2021 - Ardi Rahmanto; Hera Heru Sri Suryanti; Ratna Widyaningrum (JURNAL SINEKTIK, 2021)
This research aims to analyze about the implementation, constraints, and efforts of teachersto optimize online learning of students of class Vof Cemoro State Elementary School Boyolali District 2020/2021. The research method used is qualitative research. The results of this study are: 1) the implementation of online learning teachers do learning planning by making   RPP, teaching materials, and videos sent to   WhatsApp groups.  Then teachers use WhatsApp to communicate with learners and parents to find out the learning development of learners. This app is used.   Providing evaluation to measure the understanding of learners on online learning with Whatsapp,2) Online learning constraints are that learners cannot follow learning optimally due to the absence of unpreparednessand lack of supervision, assistance from parents, learners do not have smartphones    as well as internet packages to follow online learning, 3) Teacher efforts to optimize online learning are:create  WhatsApp groups of learners, co-ordinate and coordinate with parents,  anddo  home visit  settwice a week.